(untitled) (Applied Biological Research, 2024)
Tribal communities of West Bengal (India) are generously distributed in the major geographically distinct regions in easily distinguishable habitats. Most of these tribes prefer a non-urban lifestyle, both in the context of their livelihood and the maintenance of their diet. Here, we report the gut bacterial assemblages along with the dietary habits of Proto-Australoid Sabar tribes of Purulia, Jhargram, and their adjacent villages, along with the foothill Mech tribes of Mongolian descent of North Kamakhyaguri in West Bengal.Anthropometric measures such as height, weight, and BMI were evaluated to understand the nutritional status of participants. In order to evaluate gut bacterial assembly, 16S rRNA from the first fecal matter was subjected to Illumina Miseq™ sequencing. Quality control (FASTQC), taxonomic (QIIME2), and functional (iVikodak) profiling were performed for metagenomic analysis.The study revealed that Holdemanella, Catenibacterium, and Bacteroides exhibited the highest abundances of 11.03%, 20.50%, and 35.91% across the Sabar male, female, and kid, respectively; while Prevotella, Bifidobacterium, and Bacteroides exhibited the highest abundances of 40.51%, 17.8%, and 29.96% across the Mech male, female, and kid, respectively.This study evaluated the interplay between dietary practices, indigenous lifestyle, gut bacteriome structure, and function in the Sabar and Mech tribes.